2009
DOI: 10.1007/s00167-009-0795-z
|View full text |Cite
|
Sign up to set email alerts
|

A 3-portal approach for arthroscopic subtalar arthrodesis

Abstract: We present a 3-portal approach for arthroscopic subtalar arthrodesis with the patient in the prone position. The prone position allows the use of the two standard posterior portals and it allows for accurate control of hindfoot alignment during surgery. Furthermore, the introduction of talocalcaneal lag screws is easy with the patient in this position. In addition to the standard posterior portals, an accessory third portal is created at the level of the sinus tarsi for introduction of a large diameter blunt t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 16 publications
4
50
0
1
Order By: Relevance
“…The AOFAS score improved from 36 to 86 (9). Carro et al (15) and Beimers et al (10) reported a 100% fusion rate in 2 small series of 4 and 3 patients, respectively. El Shazly et al (16) also reported a 100% fusion rate in 10 patients after a mean interval of 11 weeks and an improvement in the AOFAS score from 38 to 74.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The AOFAS score improved from 36 to 86 (9). Carro et al (15) and Beimers et al (10) reported a 100% fusion rate in 2 small series of 4 and 3 patients, respectively. El Shazly et al (16) also reported a 100% fusion rate in 10 patients after a mean interval of 11 weeks and an improvement in the AOFAS score from 38 to 74.…”
Section: Discussionmentioning
confidence: 96%
“…In 2000, van Dijk et al (8) described posterior arthroscopy using posterolateral and posteromedial portals. Since then, these 2 portals (with or without a third portal) have been used for arthroscopic subtalar arthrodesis by several surgeons (6,(9)(10)(11). Although concerns regarding the safety of these portals have been raised, the thorough understanding of the ankle anatomy and the relationship of the arthroscopic portals to neurovascular structures at risk makes this approach relatively safe (12).…”
Section: Introductionmentioning
confidence: 99%
“…It allows a better assessment of the calcaneus valgus during screw insertion, and placement of the screws from the calcaneus posteriorly is convenient as intraoperative imaging by fluoroscopy from behind can be easily obtained. Six series, including a total of 54 patients, have been published using this technique [1,2,4,5,8,12]. All the authors report a fusion rate of 100%, Amendola et al who observed one non-union out of 11 cases [2] and Lee et al who found one non-union out of 16 cases [12].…”
Section: Discussionmentioning
confidence: 99%
“…Van Dijk et al described a posterior twoportal arthroscopic approach for the hindfoot in the prone position which provides safe access, superior visualisation of the posterior talocalcaneal facet and easy fixation of posterior screws [15]. This technique also seems to provide good clinical outcomes and a union rate similar to open techniques, but we found only six series in the literature reporting the union rate assessed on conventional X-rays after posterior subtalar arthrodesis (PASTA) [1,2,4,5,8,12]. To our knowledge, no study has reported the percentage of bone fusion on CT after PASTA.…”
Section: Introductionmentioning
confidence: 88%
“…To approach the posteromedial part of the posterior subtalar joint, posterolateral and posteromedial portals can be used [4][5][6][7] . These portals are made when posterior ankle arthroscopy together with subtalar arthroscopy is performed.…”
Section: Portalsmentioning
confidence: 99%